Non-doped phosphor for WLED with high CRI and R9 - Dang, Thi To Nu; Nguyen, Minh Thong; Nguyen, M.C.H.P. Lan; Dao, Xuan Viet; Le , Thao Vien (Hue University Journal of Science: Natural Science, 2023)
The effect of the ZnO/SnO2 ratio on phase formation and optical properties of the Zn-Sn-O compound was investigated by varying the ZnO/SnO2 molar ratio (ZnO/SnO2 = 1:2, 1:1, 2:1, 3:1, and 4:1). All samples were synthesised with high-energy planetary ball milling, followed by calcination at 1000 °C in the air. The result from X-Ray diffraction patterns (XRD) shows that the single-phase Zn2SnO4 is achieved at the ZnO/SnO2 ratio of 2:1. Whereas, the mixed phase of ZnO and Zn2SnO4 formed when ZnO is more than SnO2 (3:1 and 4:1). On the other hand, the XRD patterns of the products obtained at a ratio where SnO2 is more than ZnO present a mixture of SnO2 and Zn2SnO4. The photoluminescence of the two samples with the ratio of 2:1 and 1:3 gives full-visible range spectra from 400 to 800 nm, which are in the blue-far-red region centred at about 514, 580, and 690 nm. Temperature-dependent luminescence measurements were also carried out in this work, and the results indicate that the prepared phosphor Zn-Sn-O at the ZnO/SnO2 ratio of 1:2 has thermal stability. The obtained material was used to coat near UV LED chips, and the WLED possesses the highest CRI of 95. The SnO2-Zn2SnO4 powder can be used as a phosphor for WLED applications with high CRI and R9.